2008
DOI: 10.1128/aem.00083-08
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Parasitic Relationship between Legionella pneumophila and a Free-Living Amoeba ( Acanthamoeba castellanii )

Abstract: We analyzed the effects of temperature on the interaction of Legionella pneumophila with Acanthamoeba castellanii. At <20°C, overexpression of type 1 metacaspase, a stimulator of A. castellanii encystation, was associated with a reduced number of bacteria within amoeba. At low temperatures, A. castellanii seems to eliminate L. pneumophila by encystation and digestion.The intracellular pathogen Legionella pneumophila causes Legionnaires' disease and exploits aquatic protozoa for replication. L. pneumophila is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 21 publications
6
50
0
1
Order By: Relevance
“…Moreover, at a 100 MOI, significant Lp CFU increases were observed as early as day 1 at 30°C incubation, compared to day 2 levels at 25°C ( Figure 4C, P < 0.001) confirming the observations from previous studies that Legionella infectivity of FLA is temperature dependent [29,32].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, at a 100 MOI, significant Lp CFU increases were observed as early as day 1 at 30°C incubation, compared to day 2 levels at 25°C ( Figure 4C, P < 0.001) confirming the observations from previous studies that Legionella infectivity of FLA is temperature dependent [29,32].…”
Section: Resultssupporting
confidence: 80%
“…Previous studies have reported the temperature-dependent bacterial infectivity of FLA. Depending on the bacteria species, at low temperatures (<20-30°C), bacteria were actively digested, displayed low amplification rates, and/or eliminated from the FLA, A. polyphaga or A. castellanii; however, at higher temperatures (25-37°C), the amoeba was parasitized by the same strain of bacteria [29][30][31]. Thus, in this study, the higher MOI and temperature were used for the evaluation of the putative infectivity of virulent Schu4 and NY98 strains for the FLA cells.…”
Section: Resultsmentioning
confidence: 99%
“…For the generation of L. pneumophila UNC, PE cells were washed two times in sterilized tap water and subsequently inoculated in sterilized tap water to an OD660 of 0.3, corresponding to ϳ2 ϫ 10 8 CFU/ml. The water microcosms were statically incubated at 42°C to induce VBNC bacteria as described elsewhere (41). To study the effect of temperature for efficient generation of VBNC L. pneumophila, samples were incubated at 4°C, 21°C, 42°C, and only the latter condition lead to loss of culturability and maintenance of viability in a reasonable time (ϳ110 days).…”
Section: Methodsmentioning
confidence: 99%
“…The uptake and growth of Legionella within acanthamoeba is temperature sensitive. 9 Acanthamoeba castellani would encyst at 15°C, up to 20°C digests L. pneumophila, at 25°C-35°C the bacteria replicate freely 10 and at 37°C and above lyses the protozoa. 11 A stable relationship exists between Odyssella thessalonicensis and amoebae at 20°C but at 30°C-37°C it lyses the amoeba.…”
Section: Ulceransmentioning
confidence: 99%